The Technique for Manufacturing Flexible Electromagnetic Shields Based on Resistive Materials - H. Ayad (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2023)
The article introduces the technique for manufacturing flexible electromagnetic shields based on resistive materials (powdered charcoals and sheet foil), as well as the results of experimental justification of the use prospects of this technique in the development of new functional materials. This justification consisted of: 1) manufacturing of the experimental samples in accordance with the presented technique; 2) carrying out the measurements of the electromagnetic radiation reflection and transmission coefficient values in the frequency range of 0.7–17.0 GHz of the manufactured experimental samples. It was discovered that flexible electromagnetic shields based on the powdered charcoals manufactured in accordance with the presented technique are characterized by the electromagnetic radiation reflection coefficient values in the frequency range of 0.7–17.0 GHz, reaching –10.0 dB, when electromagnetic radiation reflection coefficient values reach –20.0 dB . Due to this fact it is possible to recommend to use them in order to ensure electromagnetic compatibility of radioelectronic equipment and to protect people from exposure to radiation, emitted by such equipment, as well as to hide ground objects from detection in the radar wavelength range.